Implementasi Pengembangan Kurikulum Tahfidz Al-Qur - Nafi'ah, Siti Anisatun; Fitri, Rizki Rahma (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2022)
The curriculum in the scope of education plays a crucial role. Currently, a trend among communities is the Qur'an memorization (tahfidz) curriculum. The Directorate General of Islamic Education has made specific policies regarding innovation and curriculum development for educational units. One of them is the development of the Qur'an memorization curriculum. The Qur'an memorization curriculum at MI NU Waturduwun has been implemented for two years. The purpose of this research is to examine the implementation of the Qur'an memorization curriculum development at MI NU Waturduwun, as well as the supporting and inhibiting factors affecting the development of the curriculum. The research method used is a case study. Data collection techniques in clude interviews and observations. The data analysis technique used is the Miles and Hubberman model. Based on the research results, the implementation of the Qur'an memorization curriculum development at MI NU Waturduwun uses the curriculum structure in group B, namely time allocation, learning resources, learning design, and local content. In the implementation of the Qur'an memorization curriculum development, there are changes in the learning load and the replacement of class hours. In the implementation of the Qur'an memorization curriculum development, there are several supporting and inhibiting factors that influence it. Supporting factors include competent human resources, support from the school principal, stakeholders, and the local community, adapting the Qur'an memorization load to the needs of students, and time allocation. Inhibiting factors include students' difficulty in memorizing Qur'anic verses, lack of supportive media, and lack of standardized learning evaluation. The implementation of the Qur'an memorization curriculum is able to attract parents' interest in enrolling their children at MI NU Waturduwun with the aim of enabling their children to memorize the Qur'an.